p+10=107+13

Simple and best practice solution for p+10=107+13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for p+10=107+13 equation:


Simplifying
p + 10 = 107 + 13

Reorder the terms:
10 + p = 107 + 13

Combine like terms: 107 + 13 = 120
10 + p = 120

Solving
10 + p = 120

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + p = 120 + -10

Combine like terms: 10 + -10 = 0
0 + p = 120 + -10
p = 120 + -10

Combine like terms: 120 + -10 = 110
p = 110

Simplifying
p = 110

See similar equations:

| 3w+9=-2w-8 | | (2x+7)+(5x+8)= | | 16=2(6)+2w | | 3x+89=12x-10 | | 2n+36=3n+4+16 | | (p+10)+(3p-13)+p=532 | | 18a-5a=8a/8 | | 246-7x=38x+16 | | 3n+4=1n+22 | | -10t-4=-8+9t | | -45=6x+9 | | (.75)(c)+(.40)(600-c)=380.00 | | 5n=2n+30 | | 55=2l+2(7) | | 1/2/4 | | 2n-9=11 | | 5+t=13+9 | | (1/2)/4 | | 3/2x+2/3x=13 | | 5+11x=86 | | 1x+2+2x=3+1 | | Q=x+y+zfory | | 6x+133=103-6x | | 6x+13=103-6x | | 3sqr(x+5)=2sqr(7-2x) | | 3w+9=2w-8 | | 11x=-x-24 | | 2x+x+1=4x-18 | | 4ln(x+4)=-4 | | 1.7-2.3=4.5z-3.5z-0.2 | | 9x-65=7x+4 | | 11d+6=8d+21 |

Equations solver categories